IMPLEMENTASI PSAK SYARIAH NO. 109 PADA ORGANISASI PENGELOLAAN ZAKAT DAN INFAK/SEDEKAH DI BAITUL MAL KOTA BANDA ACEH - Rahmi, Elia; Bustamam, Bustamam (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2019)
The research aims is analyze the accordance of the statement of islamic financial accounting standards (SFAS Sharia) Number 109 amil zakat institution and in infaq/alms at Baitul Mal In Banda Aceh City with the concept of recognition and measurement, presentation, and disclosure. The research method used is qualitative descriptive. The type of data used is qualitative data, that is by way of field study method consisting of, observation, interview, and company documentation. The results of this study indicate that the aplication of zakat in infaq/alms and accounting treatment at Baitul Mal in Banda Aceh City have not all been in accordance with statement of islamic financial accounting standards (SFAS Sharia) Number 109.